National Legal Framework to Protect the Right to Health and Right to Provide Health Care during the Covid Emergency Situation in Latvia - Olsena, Solvita; Kadile, Laura (Medicine, Law & Society, 2021)
Global public health emergency due to the spread of Covid-19 required the government of Latvia to implement necessary measures to control the virus. Numerous measures were introduced as novel legal requirements for the general public as well as for users and providers of health care. Numerous legal provisions established restrictions on the rights of patients and health care institutions. Our study aimed to explore how a human rights-based approach might be and is integrated into national responses to the Covid pandemic in health care in Latvia during the first emergency situation lasting from 12 March to 9 June 2020. Our research showed that restrictions on the right of patients to receive and the right of health care institutions to provide health care services were introduced broadly. We established that the legal requirements for restricting human rights in health required by the Constitution of Latvia were not observed.
Keywords: Covid-19, Human rights, Constitution of Latvia, right to health, right to provide health care services